Zeta potentials of polydimethylsiloxane surfaces modified by polybrene of different concentrations. Issue 4 (15th January 2016) - Song, Yongxin; Li, Jun; Li, Dongqing
Abstract : Zeta potential is an important parameter for characterizing the electrokinetic properties of a solid–liquid interface. In this paper, zeta potentials of polydimethylsiloxane surfaces modified by polybrene (PB) solutions of different concentrations in Phosphate buffer solution and pure water were reported. The zeta potentials were measured by an induction current method. The measurements were validated both by a calibration curve based on the data reported in the published papers and by comparing the zeta potential determined by using the Smoluchowski equation and the measured velocity of the electrokinetic motion of particles in a microchannel.